2016
DOI: 10.1016/j.canlet.2015.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Farnesoid X-receptor in breast cancer cell lines results in cytotoxicity but not increased migration potential

Abstract: Breast cancer is the commonest form of cancer in women, but successful treatment is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Other studies have shown FXR protein expression in these cell lines and tumors using Western blot analysis and IHC (27,(44)(45)(46). As a general finding, FXR signaling in these cell lines led to oncosuppressive effects (27,44,45). Consistent with these observations, high FXR expression in human breast tumors was associated with favorable patient survival in one analysis (46).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Other studies have shown FXR protein expression in these cell lines and tumors using Western blot analysis and IHC (27,(44)(45)(46). As a general finding, FXR signaling in these cell lines led to oncosuppressive effects (27,44,45). Consistent with these observations, high FXR expression in human breast tumors was associated with favorable patient survival in one analysis (46).…”
Section: Discussionsupporting
confidence: 67%
“…S8). Other studies have shown FXR protein expression in these cell lines and tumors using Western blot analysis and IHC (27,(44)(45)(46). As a general finding, FXR signaling in these cell lines led to oncosuppressive effects (27,44,45).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…LXR activation is known to inhibit proliferation of breast cancer cells 53 and FXR activation in breast cancer cells results in cytotoxicity. 54 Activated FXR can also counteract the tumour promoting ability of cancer-associated fibroblasts within the breast cancer microenvironment. 55 Therefore, one might hypothesise that the removal of LXR and FXR pathway components in control cell EVs suggests that normal proliferation occurs.…”
Section: Discussionmentioning
confidence: 99%